Tradisi Pohulo’o Pada Masyarakat Gorontalo Perspektif Hukum Ekonomi Syariah - Rizal Darwis (Institut Agama Islam Negeri Kendari, 2018)
This study discusses about the Islamic economic law system in the practice of pohulo'o in Gorontalo society. This study is examined through normative and socio-cultural approaches. Data obtained from interviews, documentation and questionnaires with 150 respondents. The results of the study show that: First, the practice of pohulo'o has basically produced a lot of pawn (al-rahn) in the sharia economic legal system, both related to harmony and its requirements; Second, the relevance of pohulo'o between the concept of al-rahn in the Islamic economic law system is related to: (a) the existence of a contract from the terms and conditions which have similarities; (b) the practice of pohulo'o with conservation of pawnshops (upilohulo'o) which tends to be carried out by the pawn holder (popohulo'o), although it is a pawn (tampohulo'o) and may also use it. However, in this case it depends on the agreement or contract that has been made. Ulama differs their views on this matter.